PENERAPAN PRODUKSI BERSIH UNTUK PENANGANAN AIR TERPRODUKSI DI INDUSTRI MINYAK DAN GAS - Sillak Hasiany; Erliza Noor; Moh. Yani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Produced water is the largest volume waste from oil and gas productions especially from old well and had a complex mixture of organic and inorganic compounds like BTX, phenol, and TDS. The untreated produced water discharges may be harmful to the surrounding environment, so is necessary to have produced water management that tend to have  reduce a risk for the enviroment and human. Cleaner Production (CP) is a continuous application of an integrated, preventive, environmental management strategy to increase overall efficiency and to reduce risks to humans and environment. the aims of this research are (1) identify cleaner production opportunities from produced water management  which can be implemented in company (2) solved a problem from existing produced water management. Research can be done by primary and secondary data collecting direct field observation, and laboratory analyze of produced water. Analysis were done by using Quick Scan that consisted in two phase, preparation and implementation, evaluation of Cleaner Production opportunities and evaluation of environmental and economic assessment. The result showed that Produced water is the largest volume waste from oil and gas production with a total value worth 3.939.370 barel for 2012 and also water injection is the most effectif and effcien technology to manage produced water than those other surface discharge methods for company. Replacement of produced water pipes from type B to type A is the application of Cleaner Production opportunities in companies that benefit from the economic and environmental. Keywords: produced water, cleaner production, water injection